FACTORS INFLUENCING THE BEHAVIOR OF CONDUCTING BREAST SELF-EXAMINATION ON WOMEN OF CHILDBEARING AGE IN THE BANDUNG HEALTH CENTER AREA SERANG REGENCY IN 2023 - Sri Nani Indriyani; Prihayati; Lukman Waris (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
Global Buren of Cancer data shows data on cancer patients in the world as many as 19.3 million cases. The highest number is in breast cancer patients totaling 2.261 million cases (Globocan, 2020). Data from the International Agency for Research on Cancer (IARC) in 2020, the number of new cases of breast cancer has increased and become the highest incidence of cancer in women, namely breast cancer with 665,339 new cases and 131,252 deaths from breast cancer worldwide (Globocan, 2020). The low desire of women to do BSE examination can be influenced by internal and external factors. Internal factors include knowledge, attitudes and family history of cancer. As for external factors, namely sources of information and parental support. This type of research is quantitative research with a research design using a cross sectional approach. The purpose of this study is to determine the factors that influence the behavior of conducting breast self-examination in women of childbearing age in the Bandung Health Center area, Serang Regency in 2023. By using the total sampling technique, the determination of the sample obtained was as many as 120 mothers who met the inclusion criteria. Chi Square test results show a significant relationship between knowledge, education, the role of health workers, and information media with breast self-examination behavior (P−value 0.000).